ANALYSIS OF TOURISM SECTOR DEVELOPMENT IMPACT ON SOCIOECONOMIC CONDITIONS (A CASE STUDY ON KAMPUNG WISATA KUNGKUK BATU) - Gozali, Legong (Jurnal Ilmiah Mahasiswa FEB, 2022)
The tourism sector is often used as a measuring tool to assess the level of the economy in an area. The tourism sector is one of the boosters of the level of the economy in an area. Kungkuk Tourism Village is an ecotourism sector, ecotourism itself is tourism that aims to preserve protected friends by providing economic opportunities to the surrounding community. This study aims to analyze the impact of Kungkuk Tourism Village on the socioeconomic conditions of the community. By using quantitative research methods and using a descriptive approach, as well as samples selected using purposive techniques in addition to 60 samples. The variables used in this study were 5 indicators, namely health, hygiene, safety, consumption level and income. By using the Wilcoxon test and the different t test, it can be seen the difference before and after the existence of the Kungkuk Tourism Village. By using the different test T test the results of consumption patterns showed significant results (p = 0.000) so it can be concluded that there are significant differences. And the Wilcoxon test results show that income, health, safety and cleanliness experienced significant changes before and after the existence of the Kampung Wisata Kungkuk. With the results of income (p = 0.000), health (p = 0.000), security (p = 0.000), cleanliness (p = 0.000) p = 0.721. From the results of the researcher's analysis, it can be concluded that p value < 0.05 there is a significant difference before and after the existence of Kampung Wisata Kungkuk, except for the cleanliness variable with a sig value. 0.721 (> 0.05) so there is no significant difference between before and after Kampung Wisata Kungkuk. The conclusion of this study is that the existence of Kampung Wisata Kungkuk has an impact on the socio-economic conditions of the surrounding community, except for the hygiene indicatorsKeyword: Ecotourism, Socio-economic, Quantitive Research Method, Kampung Wisata Kungkuk